Mechanisms of drug resistance in neoplastic cells - Woolley, Paul V., 1939-; Tew, Kenneth D. (Bristol-Myers cancer symposia, 1988)
Bristol-Myers Cancer Symposia, Volume 9: Mechanisms of Drug Resistance in Neoplastic Cells provides information on both basic scientific and clinical studies on the causes and implications of tumor cell resistance to common antineoplastic agents. The book describes the colon cancer as a model for resistance to antineoplastic drugs; mathematical modeling of drug resistance; and the mechanism of induced gene amplification in mammalian cells. The text also discusses the cellular concomitants of multidrug resistance; resistance to alkylating agents; and the phosphoprotein and protein kinase C chan.